STUDY ON FACTORS AFFECTING THE EFFICIENCY OF MARKER-ASSISTED INTROGRESSION - J. Y. Bai (Journal of Animal and Plant Sciences, 2015)
In this paper we simulate the breeding process of marker-assisted introgressing a favorable QTL allele from “donor” to “recipient”. During this process, the foreground selection and background selection were made for introgression population simultaneously: foreground selection is making indirect selection of target gene by its closely linked two flanking markers, four selection methods including random selection, genomic similarity selection, index selection and MBLUP selection are used in background selection, and the MBLUP was first used in background selection. The effect of different factors on the efficiency of marker-assisted introgression a QTL was simulated in this study, the factors include different background selection methods (random selection, genomic similarity selection, index selection and MBLUP selection), population sizes (500 and 1000), ratios of QTL variance (10% and 30%). The following results were obtained: (1) Genomic similarity selection and index selection can make recipient genome recover entirely through 3～4 backcross generations, though MBLUP selection could not make recipient genome recover quickly, it can get the most genetic responses for background traits. (2) Enlarging population size can increase frequency of favourable allele for introgressing QTL and genetic responses for background traits. (3) Enlarging ratio of QTL variance can increase both frequency of favourable allele for background QTL and genetic responses for background traits.
Keywords: Marker-assisted introgression; Foreground selection; Background selection; MBLUP